HUBUNGAN AKSES INFORMASI, KUALITAS, DAN INFRASTRUKTUR TERHADAP EFISIENSI DISTRIBUSI RANTAI PASOK LELE DI KABUPATEN NGAWI: ANALISIS NON-PARAMETRIK SPEARMAN RANK - Atmojo, Titin Andriyani; Puspita, Helda Jaya (ANALISIS, 2025)
This study aims to determine the monotone association between access to information and distribution efficiency; the monotone association between product quality and distribution efficiency; and the monotone association between infrastructure and distribution efficiency. The research was conducted in Ngawi Regency and involved 61 agribusiness actors (farmers and collectors) as respondents. The respondents were selected using a purposive sampling method. Data were collected through respondents’s responses by answering a questionnaire distributed via Google Forms. The data were subsequently analyzed using the Spearman Rank Correlation test to identify the correlation between each independent variable and the dependent variable. The results of the respondent characteristics indicate that the majority of agribusiness actors were in the age group of 36–55 years (34.43%), with male gender (77.05%), and had completed a senior high school education (54.10%). The Spearman Rank Correlation tests shows that access to information has a positive and statistically significant correlation with distribution efficiency at a moderate strength. By contrast, product quality has a positive but very low strenght and non-significant correlation with distribution efficiency. Meanwhile, the Infrastructure variable has a possitive correlation with low strength and significant correlation with distribution efficiency.